Телевизийн хөгжөөнт нэвтрүүлгийн загварыг академик англи хэлний хичээлд ашигласан туршилт судалгаа: Using TV entertainment show models in an academic review lessons for intermediate level - B., Ariuntuul; N., Tserendejid (Mongolian Journal of Foreign Languages and Cultures, 2023)
Nowadays, we are trying to teach academic English which covers a variety of academic disciplinary areas, with a comprehensive program in a tight schedule. It is hard to use activities which are interesting and engaging but require a quite long time in every lesson. Students should develop the ability to read texts on familiar, basic academic topics covering psychology computer and information technology, sociology, geology, humanity and ethical issues in scientific research with an emphasis on vocabulary expansion and application of critical reading skills in intermediate academic level. They review basic English sentence structures and develop the ability to write accurate, fluent, multiple sentences about basic academic topics with an emphasis on the use of specific detail and sentence combining in paragraphs and essays. In Oral Communication, Students need to develop speaking and listening skills necessary for participating in classroom discussions and expressing their opinions with critical listening skills. The most appropriate activity which can meet requirements of recalling, reviewing and reinforcing what they learn in a short period of time is a quiz, a form of game or mind sport in which participants attempt to answer questions correctly. There are many activities which improve students’ motivation and attention, make lessons more active, more engaging and more fun, such as Hangman, Bingo, Where is ….? etc. But, the method we experimented enables to include a full semester and an academic year’s contents and is distinctive to cover all skills (reading, writing, listening and speaking). It can be very interesting, effective, motivating and reinforcing. After teaching experimental lesson which based on this pattern, we studied the results while comparing the experimental class to checkpoint class. Here we present the compared results of exam grade and student satisfaction survey after taking exam according to the topics which we reviewed in the experimental lesson.